ANALGESIC TEST AND TOXICITY OF n-HEXANA FRACTION TREMBESI LEAVES (Samanea saman (Jacq.) Merr.) IN MICE (Mus musculus L.) - Rosa Juwita Hesturini; Krisna Kharisma Pertiwi; Meylisa Nurvita Astari; Adellia Ayu Febriana (Jurnal Farmasi Sains dan Praktis, 2022)
Trembesi plant (Samanea saman (Jacq.) are used for traditional medicine as an antibacterial, an analgesic, treat headaches and diarrhea. The aims of this research were to determine analgesic activity and toxicity of n-hexana fraction of trembesi leaves in mice. Extraction using maceration method with 70% ethanol solvent, then solid-liquid partitioned. The activity of an analgesic test by induction acetic acid 1% using negative control CMC Na 0,5%, positive control acetosal dose of 360 mg/kgBW, the treatment group n-heksana fraction doses of 200, 350 and 500 mg/kgBW, while the toxicity test used negative CMC Na 0,5%, with the treatment group dose 5, 50, 500 and 5000 mg/kgBW. Analysis analgesic test data using the Hendersot and Forsaith equations for know the amount of stretching mice. Observation irritation gastric done by observation in makroskopis. While the toxicity test is done within 24 hours for calculated LD50 and make observations and Kruskal-Walli’s test in time 7 days to find out the delayed toxic effects. The results obtained the percent of the analgesic of the n-heksana fraction by 37.86%, 55.78% and 70.9% and LD50 values of 5000 mg/kgBW with the results observations made no significant difference (p>0.05). This research conclusion was the n-hexana fraction trembesi leaves having an analgesic doses activity with effective 350 mg/kgBW with a 55,78% analgetika potential and a toxic effect are categorized as toxic mild and there is no on the irritation.